2009
DOI: 10.1038/nchem.288
|View full text |Cite|
|
Sign up to set email alerts
|

Size-specific catalytic activity of platinum clusters enhances oxygen reduction reactions

Abstract: Colloidal platinum nanoparticles with diameters of 2-5 nm on carbon supports are currently regarded as the best catalysts for the oxygen reduction reaction. However, the particle size is limited by the conventional preparation methods that are used to synthesize small platinum particles; the inherent activity of ultrasmall nanoparticles has not yet been revealed. We present a practical synthesis for ultrafine subnanometre platinum clusters using a spherical macromolecular template with no disorder in molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
428
0
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 532 publications
(439 citation statements)
references
References 41 publications
4
428
0
7
Order By: Relevance
“…In 2009, by using a phenylazomethine dendrimer, Yamamoto et al successfully prepared a series of platinum clusters with a defined number of atoms [46]. The ORR activity of the Pt 12 @3, Pt 28 @3 and Pt 60 @3 (3 = phenylazomethine) clusters is shown in Table 2.…”
Section: Pt Clusters For Orrmentioning
confidence: 99%
“…In 2009, by using a phenylazomethine dendrimer, Yamamoto et al successfully prepared a series of platinum clusters with a defined number of atoms [46]. The ORR activity of the Pt 12 @3, Pt 28 @3 and Pt 60 @3 (3 = phenylazomethine) clusters is shown in Table 2.…”
Section: Pt Clusters For Orrmentioning
confidence: 99%
“…The purpose of the current study is to investigate ORR mechanisms on defective graphene−supported Pt nanoparticles using density functional theory (DFT) calculations coupled with a computational hydrogen model (CHE) 2 to provide information regarding the stability of possible intermediates within the electrochemical reaction pathways. Although metal nanoparticles used for the ORR applications are deposited on various substrates (e.g., usually carbon supports), 25,26 we compare our O 2 adsorption and reactivity results to free Pt 13 nanoparticles to demonstrate the effect of a defective graphene support on the catalytic activity of Pt 13 nanoparticles. In addition, details of the structural and electronic properties of these systems are discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Platinum is perhaps one of the most important metals in catalysis applications. Recently, it has been reported that sub-nanometer Pt [8][9][10] NCs stabilized on high-surface-area solid supports are 40-100 times more active for the oxidative dehydrogenation of propane than the previously studied platinum catalysts, 8 which is responsible for their surprisingly high surface reactivity of Pt NCs. However, very few attempts have been made at the difficult synthetic route of platinum nanoclusters (Pt NCs) in solution.…”
mentioning
confidence: 99%